Legal regulation of rational energy production and consumption in Russia and other states (Nexo Revista Científica, 2021)
The authors of the article analyze the problems of legal regulation of rational subsoil use and energy consumption in Russia, Germany, USA, Japan and other countries. It also compares the energy legislation of different countries. Based on the results, it was concluded that the development of the legislation of these countries is in general compliance with the strategic goals in the field of energy production and consumption. These goals are the construction of ecologically clean "green" energy based on the rational use of mineral resources and minerals and the rational and efficient distribution of energy.